Lost links : - Wexler, Daniel (Clock Tower Press, 2003)
Literally hundreds of classic courses from golf’s pre-World War II Golden Age have vanished over the years, including nearly 200 designed by legendary architects like Donald Ross, A.W. Tillinghast and Dr. Alister MacKenzie. In this sister volume to his award-winning book, The Missing Links, historian Daniel Wexler profiles more than 70 of the ver y best courses and holes in America, bringing them back to life with detailed histories, color maps and period photographs. Within Lost Links, the reader can walk William Flynn’s sand-strewn North course at Boca Raton, skirt towering Pacific cliffs at Billy Bell’s mysterious Royal Palms, retrace Seth Raynor’s footsteps at the Greenbrier and revisit George Thomas’s legendary lost holes at La Cumbre